Anti-SARS-CoV-2 antibody testing in IBD healthcare professionals: are we currently able to provide COVID-free IBD clinics? - Malickova, Karin; Kratka, Zuzana; Luxova, Stepanka; Bortlik, Martin; Lukas, Milan (Scandinavian journal of gastroenterology, 2020)
Coronavirus disease 2019 (COVID-19), caused by Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2), has spread worldwide triggering a pandemic during the year 2020. The proportion of persons infected with SARS-CoV-2 whose infection remained subclinical is not known. However, such information is important to determine whether the control measures currently employed are sufficient to halt the spread of the virus. Current study has examined the seroprevalence of anti-SARS-CoV-2 antibodies in a population of 92 healthcare professionals working with patients with inflammatory bowel disease (IBD). The enzyme-linked immunosorbent assay (ELISA) test system for SARS-CoV-2 IgG from EUROIMMUN Medizinische Labordiagnostika AG (Germany) was used. Very low herd antibody-mediated immunity was proven, less than 2%, although we have been faced with the COVID-19 pandemic for several months. Anti-SARS-CoV-2 IgG antibody testing is currently unable to provide sufficient information about our anti-infectious immunity.
Keywords: Clinical Laboratory Techniques; kolektivní imunita; hodnocení rizik; Immunoglobulin G; Male; protilátky virové; Infectious Disease Transmission, Patient-to-Professional; Risk Assessment; Seroepidemiologic Studies; séroepidemiologické studie; Health Personnel; Inflammatory Bowel Diseases; koronavirové infekce; imunoglobulin G; mužské pohlaví; přenos infekce z pacienta na zdravotnického pracovníka; pandemie; Ambulatory Care Facilities; ELISA; zdravotnický personál; idiopatické střevní záněty; klinické laboratorní techniky; Germany; virová pneumonie; hygiena práce; Enzyme-Linked Immunosorbent Assay; lidé; ženské pohlaví; Humans; Německo; epidemický výskyt choroby; Occupational Health; odhad potřeb; Needs Assessment; ambulantní zařízení; Pneumonia, Viral; Antibodies, Viral; Immunity, Herd; Pandemics; Disease Outbreaks; Coronavirus Infections; Female